The Pitch Lake, La Brea, Trinidad. B.W.I. - (:unkn) unknown (My University, 2010)
In this antique postcard one sees a close up view of the surface of the Pitch Lake which looks like an elephant’s skin. Gullies on its surface are filled with rainwater, tufts of grass grow here and there and forest trees lie on the horizon. A few oil derricks rise above their canopy.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Brighton; Cities and towns--Trinidad and Tobago--La Brea; Asphalt industry--Trinidad and Tobago; Pitch; Forests and forestry--Trinidad and Tobago; Oil well drilling rigs--Trinidad and Tobago; Ponds--Trinidad and Tobago; [1931]; Pitch Lake, The (La Brea)